Emanuel Ringelblum przed wojną: człowiek i historyk - Kassow, Samuel (Zagłada Żydów. Studia i Materiały, 2007)
This article discusses the pre-war life of Emanuel Ringelblum – from the organisation of the Junger Historiker Krajz (the circle of young Jewish historians) at Warsaw University, through his YIVO activity, his involvement in the setting up of tourist associations, work for the Joint Distribution Committee as editor-in-chief of „Folkshilf”, active membership in Poale Zion-Left (he ran its most important education agency: the Ovnt kursn far arbiter) to his involvement in organisation of aid for Jews in the transit camp in Zbąszyń in 1938.